RANCANG BANGUN MESIN PENGAYAK PASIR GUNA MENINGKATKAN KUALITAS PENGAYAK PASIR UNTUK KONSTRUKSI BANGUNAN - Napitupulu, Robert; Herwandi, Herwandi; Hernawan, Sutrisno; Rio, Rio Pratama; Purma , Purma (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The increasing demand for construction materials, particularly sand, continues to rise in line with the rapid development of infrastructure. Manual sand sieving is still widely used, especially in rural areas, but it has proven to be inefficient due to its labor-intensive nature, time consumption, and limited capacity. Therefore, this final project focuses on designing and building an automatic rotary sand sieving machine with a capacity of 130 kg/hour. The machine is powered by a 5 HP gasoline engine and utilizes a belt and pulley transmission system, combined with a sand mesh size of 6 (2.83 mm). The design process adopts the Research and Development (R&D) method, consisting of problem identification, data collection, design, manufacturing, assembly, testing, and user validation. Based on testing results, the machine is capable of producing consistently fine sand suitable for wall plastering in construction. One of the key advantages of this machine lies in its ease of maintenance, especially in replacing the sand mesh, allowing users to adapt the sieve size according to specific requirements. Furthermore, technical calculations such as torque estimation, motor power, angular velocity, and system efficiency have been comprehensively conducted to ensure optimal performance. The implementation of this machine is expected to significantly improve work productivity, reduce reliance on manual labor, and enhance time and cost efficiency in the sand sieving process at construction sites.